The Correlation of Blood Glucose Levels Measurement by Using Laser Speckle Imaging (LSI) Method - Zulkarnain (Journal of Technomaterial Physics, 2019)
Laser Speckle Imaging (LSI) method is the imaging of light interference events when it interacts on a rough surface. A laser beam which entered the surface of skin will experience reflection, refraction and scattering. Interaction between a laser beam with the surface of the skin when entering to membranes blood, provides contrast information that were resulted from the rays scattered in a certain position, recorded by a CMOS camera and translated by imageJ program. A picture will provide an information of the intensity from certain skin areas with dark light pattern which keeps blind due to the presence of blood flow that does not dwell. The result of contrast imaging was validated with direct measurement by blood glucose device. The objects were people with the age range of 17 until 63 years old. This study aims to find the correlation between contrast Speckle to blood sugar levels in the human body. The result revealed that correlation between contrast intensity of red, green and blue to glucose level are 0.3275; 0.3165; 0.3050 respectively, and then correlation between contrast intensity to age are 0.6410; 0.6554; 0.6526. The data indicated high correlation on contrast to age and average correlation on contrast to glucose blood level.